Underwritten Dividend Reinvestment Plans and Conflicts of Interest. (October 2016) - Pricha, Nicholas; Foley, Sean; Partington, Graham; Svec, Jiri
Abstract: We examine conflicts of interests arising from the pricing of seasoned equity offerings (SEOs) in underwritten dividend reinvestment plans (DRIPs). A DRIP is a type of SEO that enables shareholders automatically to reinvest their dividend entitlements in the issuing company's shares. The underwriters have an incentive to sell stock during the DRIP pricing period in order to hedge price risk and/or to reduce the price at which shares are issued. Using individual brokers' transactions, we show that underwriting brokers engage in an abnormally high level of selling during the issue pricing period. Comparison of pricing period returns between stocks with underwritten DRIPs and a matched sample of non‐underwritten DRIPs shows that significantly more negative returns accrue to firms that have their issues underwritten.